Preparation method of temperature-adjustable transparent plate based on corn straw
By purifying corn stalks and infiltrating them with epoxy resin, transparent boards with high light transmittance and temperature regulation properties are prepared, solving the problem of low cellulose content in corn stalks, realizing the efficient utilization of agricultural waste, and improving the environmental friendliness and functionality of building and product design.
Patent Information
- Application Number
- CN202511866893.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-11
- Publication Date
- 2026-02-06
AI Technical Summary
In existing technologies, corn stalks have low cellulose content, which makes it difficult to improve the temperature regulation performance and light transmittance of transparent sheets in a coordinated manner. Furthermore, the production technology of temperature-regulating transparent sheets is not yet mature, which affects the performance of high-quality products.
By purifying corn stalks, including eutectic solvent treatment, high temperature treatment, decolorization treatment and mercerization treatment, cellulose is purified, and then epoxy resin is used for infiltration and curing to prepare transparent sheets with high light transmittance and temperature regulation properties.
The corn stalk-based transparent board achieves high light transmittance and good temperature regulation performance, effectively replacing wood, reducing costs, and improving the environmental friendliness and functionality of building and product design.
Smart Images

Figure CN121471594A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cellulose composite materials technology, and in particular to a method for preparing a temperature-adjustable transparent plate based on corn stalks. Background Technology
[0002] With the improvement of production levels, people are paying more and more attention to the aesthetics of design, as well as the environmental friendliness and functionality of materials. Therefore, the development of new environmentally friendly materials that are both green and aesthetically pleasing and have good functionality is of great significance to modern architectural design, product design and other fields.
[0003] Wood fibers are abundant in nature and possess excellent optical properties—high emissivity and photothermal conversion ability—making them promising candidates for radiation-induced temperature regulation. Cellulose, a component of wood fibers, exhibits high reflectivity in the 200-2500 nm range and high emissivity in the 8-13 μm range, demonstrating excellent radiative cooling characteristics.
[0004] Corn stalks, as an agricultural waste, are of great significance for green and sustainable development through comprehensive utilization. The cellulose content of corn stalks can reach 38%, making them suitable for the production of transparent boards. However, current research on transparent boards mainly focuses on using wood such as poplar and eucalyptus as raw materials, with relatively little research on using non-wood materials such as corn stalks to create transparent boards.
[0005] This application proposes a method for preparing temperature-regulating transparent boards based on corn stalks. Using corn stalks instead of eucalyptus, poplar, and other woods can reduce the large-scale consumption of these types of wood. However, the cellulose content in corn stalks is significantly lower than that of the aforementioned woods, which increases the difficulty of cellulose extraction. Furthermore, the production technology for temperature-regulating transparent boards is still in the research and development stage, and the synergy between temperature regulation performance and light transmittance remains a key factor hindering the production of high-quality products.
[0006] Based on this, the method for preparing temperature-adjustable transparent panels based on corn stalks in this application involves effectively purifying the corn stalks, ensuring the effective purification of cellulose, and then infiltrating and filling them with epoxy resin. This process yields a building material with high ornamental value, high light transmittance, good thermal insulation performance, and great functional potential. Summary of the Invention
[0007] This invention provides a method for preparing a temperature-regulating transparent board based on corn stalks, offering a new pathway for the efficient utilization of agricultural waste. This method has excellent purification effect on cellulose in corn stalks, and the resulting green building board has significant temperature regulation and light transmission properties, making it highly valuable for application in architectural and product design fields. It also solves the problems existing in the prior art.
[0008] The technical solution adopted in this invention is: A method for preparing a temperature-adjustable transparent sheet based on corn stalks is provided, comprising the following steps: (1) Preparation of corn straw cellulose hydrogel by purification of corn straw; S1, Preprocessing Add water and a low eutectic solvent to corn stalks, raise the temperature to 165℃±5℃ within 60-70 minutes, and keep it at that temperature for 50-60 minutes; S2, High-temperature treatment Add active alkali and continue to keep warm at 165℃±5℃ for 50-60 minutes. After the reaction is complete, wash twice with 100 times the amount of tap water. S3, Decolorization treatment The product obtained in step S2 was added to NaClO2, a eutectic solvent and water, and treated in a water bath at 75°C for 100-120 minutes at pH=1.5. Then it was diluted and washed three times with 90 times the amount of tap water to obtain lignocellulose. S4, Mercerizing treatment The lignocellulose obtained in step S3 was completely immersed in a 170 g / L NaOH solution at a temperature of 20℃±1℃ for 45-60 min; then washed with 300-350 times the amount of tap water and vigorously stirred until neutral to obtain corn straw cellulose hydrogel. (2) Osmosis treatment Epoxy resin a glue, epoxy resin b glue, and dyeing solution are mixed evenly, and the corn straw cellulose hydrogel obtained in step (1) is immersed in the dyed colored epoxy resin, and the vacuum-release repeated operation is performed. (3) Curing and molding Spread the mixture obtained from step (2) evenly and allow it to cure at room temperature to obtain the final product.
[0009] Further, the eutectic solvent in step (1) is prepared as follows: oxalic acid and choline chloride are mixed uniformly in a molar ratio of 1:1 and stirred in a 90°C water bath for 1.5-2 hours until there are no impurities in the solution, and then cooled until no crystals precipitate; in S1, water is added to maintain the liquid ratio at 1:4, and the amount of the eutectic solvent in S1 is 2%-3% of the dry weight of the corn stalks.
[0010] Further, in step (1), the amount of active alkali used in the S2 high-temperature treatment is 25%-30% of the dry weight of the corn stalks in this step; the active alkali is NaOH and Na2S; the degree of sulfidation in this step is 25%-30%; and the liquid ratio is 1:4.
[0011] Furthermore, in the S2 high-temperature treatment, the amount of each active alkali used is 25% of the oven-dry weight of the corn stalks in this step; the degree of sulfidation in this step is 25%.
[0012] Furthermore, the degree of sulfidation refers to the percentage of Na2S added relative to the mass of the active alkali.
[0013] Furthermore, the mass amounts of the above-mentioned active bases NaOH and Na2S are calculated as follows: NaOH mass = dry corn stalk mass * active alkali dosage (mass percentage) * (1 - degree of sulfidation); Na2S mass = dry corn stalk mass * active alkali dosage (mass percentage) * sulfidation degree * conversion factor (78 / 80).
[0014] Furthermore, in step (1), the liquid ratio of S1 and S2 refers to the ratio of the absolute dry mass of the corn stalks processed in the corresponding step to the sum of the masses of all liquids, which is 1:4 after adding water.
[0015] Further, in step (1), the amount of NaClO2 used in the S3 decolorization treatment is 2%-5% of the dry weight of the corn stalks in this step; the amount of eutectic solvent is 6-9 times the dry weight of the corn stalks in this step; the amount of water added in S3 is such that the dry weight of the corn stalks treated in this step accounts for 10% of the total mass of all solid-liquid mixtures except for the eutectic solvent. Further, in step (2), the mass ratio of epoxy resin a to epoxy resin b is 2:1-3:1.
[0016] Further, in step (2), the staining solution is CoCl2·6H2O acetone solution, FeCl3·2H2O solution or CuCl2·2H2O solution; the amount of staining solution added is 2%-5% of the total mass of epoxy resin.
[0017] Further, in step (2), the mixing order is epoxy resin a, dyeing solution, epoxy resin b, and corn stalk cellulose hydrogel. The mixture is stirred evenly to obtain colored epoxy resin.
[0018] Furthermore, the vacuuming time in step (2) is 10-15 minutes, and it is repeated 5-10 times.
[0019] Furthermore, in step (3), room temperature curing refers to curing at 25℃-35℃.
[0020] The beneficial effects of this invention are: 1. This invention utilizes corn stalks to produce temperature-regulating transparent boards, which can effectively replace the reliance on wood in the construction and product design fields and alleviate wood consumption.
[0021] 2. The preparation method of this invention has lower cost and produces green board products with superior performance, exhibiting good transparency and temperature regulation capabilities. Although cellulose in corn stalks itself does not possess "active radiative temperature regulation" function, its high refractive index, high infrared emissivity, and porous micro / nano structure make it an ideal framework for constructing passive radiative cooling materials. The temperature regulation performance of the board obtained by this invention is achieved through purification, structural regulation, and compounding with a low-refractive-index resin to form a cellulose-resin hybrid.
[0022] 3. The preparation method of this invention specifically improves the purification efficiency of cellulose by effectively purifying corn stalks, including eutectic solvent treatment, high temperature treatment, decolorization treatment and mercerization treatment. By separating cellulose and lignin in the stalks and filling the microscopic gaps with epoxy resin, the obtained cellulose fills the cavity. After curing and molding, the resulting board is a bio-based material that can passively regulate temperature through radiation, increasing the strength of the bio-based material, with good transmission effect, diverse colors, and excellent temperature regulation performance. Attached Figure Description
[0023] Figure 1 The transmittance test results are for the sheet material prepared according to the embodiments of the present invention; Figure 2 This study examines the temperature regulation performance of the plate material prepared in Example 1 of the present invention. Detailed Implementation
[0024] To clearly illustrate the technical features of this solution, the invention will be described in detail below through specific embodiments and in conjunction with the accompanying drawings.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of this application.
[0026] The following embodiments are for illustrative purposes only and are not intended to limit the scope of this application. Experimental methods in the following embodiments that do not specify specific conditions should first refer to the guidelines given in this application, or may be performed according to experimental manuals or conventional conditions in the art, or by referring to experimental methods known in the art. Unless otherwise specified, all methods are conventional methods in the art.
[0027] In the following specific embodiments, unless otherwise specified, slight deviations may exist within the weighing accuracy range for the measurement parameters of the raw material components. For temperature and time parameters, acceptable deviations due to instrument testing accuracy or operational precision are permissible. The equipment and raw materials used are commercially available or commonly used in the art.
[0028] In the following examples, "dry weight" is only used as a reference for weighing the reagents required in each step. It does not mean that the material after the corresponding step is dried to achieve dryness. Instead, the dry weight is calculated by measuring the moisture content of the material after treatment. Then, the dry weight of the corn stalks in each step is used as the basis for weighing the corn stalks and other required reagents or components in each step.
[0029] Example 1 The method for preparing the temperature-regulating transparent sheet material based on corn stalks adopts the following operation steps: (1) Preparation of eutectic solvent: 63.0g of oxalic acid dihydrate and 69.6g of choline chloride are mixed evenly and stirred continuously in a water bath at 90℃ for 1.5h until there are no impurities in the solution and no crystals precipitate after cooling.
[0030] (2) Pretreatment of corn stalks: Weigh 100g of clean and dry corn stalks, add 2g of eutectic solvent, add deionized water to make the total (solution) mass 400g, heat for 60min, the maximum temperature is 165℃, and the holding time is 60min.
[0031] (3) High-temperature treatment of pretreated corn stalks: Weigh 100g of corn stalks obtained after the above pretreatment with an absolute dry weight, add NaOH solution prepared by adding water to 75g of NaOH and Na2S solution prepared by adding water to 24.38g of Na2S, and add deionized water to make the liquid mass reach 400g, i.e., the liquid ratio is 1:4. The high-temperature treatment temperature is 165℃ and the holding time is 60min. After the reaction is completed, wash it twice with 10L of tap water.
[0032] (4) Decolorization treatment: Weigh 100g of corn stalks obtained after the above high-temperature treatment, add 40g of 5% NaClO2 solution, add deionized water to make the total mass of the solution (solid-liquid mixture) 1000g, add 10% oxalic acid solution until pH=1.5; add 600g of eutectic solvent, adjust the water bath temperature to 75℃ and heat for 100min. After heating, dilute and wash three times with 7.7L tap water to obtain lignocellulose.
[0033] (5) Mercerization treatment: 100g of oven-dry lignocellulose after the above-mentioned high-temperature decolorization treatment is completely immersed in a 170g / L NaOH solution. The treatment temperature is 20℃ and the treatment time is 45min.
[0034] (6) The treated lignocellulose is washed with 28L of tap water and stirred vigorously until neutral to obtain corn stalk cellulose hydrogel.
[0035] (7) Infiltration treatment: Dissolve 1.2g of CoCl2·6H2O epoxy resin in 2g of acetone, mix 40g of epoxy resin a and 20g of epoxy resin b evenly, then immerse 20g of the oven-dry weight of the corn stalk cellulose hydrogel in the epoxy resin, and perform a vacuum-release cycle. The vacuuming time is 10 minutes, and the process is repeated 10 times.
[0036] (8) Curing and molding process: The corn stalk cellulose hydrogel that has been impregnated and vacuumed and released is spread out with the colored epoxy resin mixture and cured at room temperature of 30°C to obtain a temperature-adjustable transparent board based on corn stalks. The board is light red in sunlight.
[0037] Example 2 The method for preparing the temperature-regulating transparent sheet material based on corn stalks adopts the following operation steps: (1) Preparation of eutectic solvent: 63.0g of oxalic acid dihydrate and 69.6g of choline chloride are mixed evenly and stirred continuously in a water bath at 90℃ for 1.5h until there are no impurities in the solution and no crystals precipitate after cooling.
[0038] (2) Pretreatment of corn stalks: Weigh 100g of clean and dry corn stalks, add 2g of eutectic solvent, add deionized water to make the total mass 400g, heat for 60min, the maximum temperature is 165℃, and the holding time is 60min.
[0039] (3) High-temperature treatment of pretreated corn stalks: Weigh 100g of corn stalks obtained after the pretreatment with an absolute dry weight, add NaOH solution made by adding water to 75g NaOH and Na2S solution made by adding water to 24.38g Na2S, add deionized water to make the total liquid mass reach 400g, i.e., the liquid ratio is 1:4, the high-temperature treatment temperature is 165℃, the heat preservation time is 60min, and after the reaction is completed, wash it twice with 10L tap water.
[0040] (4) Decolorization treatment: Weigh 100g of corn stalks obtained after the high-temperature treatment, add 40g of 5% NaClO2 solution, add deionized water to make the total mass of the solution (solid-liquid mixture) 1000g, add 10% oxalic acid solution to pH=1.5, add 600g of eutectic solvent, adjust the water bath temperature to 75℃ and heat for 100min. After heating, dilute and wash three times with 7.7L tap water to obtain lignocellulose.
[0041] (5) Mercerization treatment: 100g of oven-dry weight of high-temperature decolorized lignocellulose is completely immersed in a 170g / L NaOH solution. The treatment temperature is 20℃ and the treatment time is 45min.
[0042] (6) The treated lignocellulose is washed with 28L of tap water and stirred vigorously until neutral to obtain corn stalk cellulose hydrogel.
[0043] (7) Infiltration treatment: Dissolve 1.2g of FeCl3·6H2O epoxy resin in 2g of deionized water, mix 40g of epoxy resin a and 20g of epoxy resin b evenly, then immerse 20g of the oven-dry weight of the corn stalk cellulose hydrogel in the epoxy resin, and perform a vacuum-release cycle. The vacuuming time is 10 minutes, and the process is repeated 10 times.
[0044] (8) Curing and molding process: The corn stalk cellulose hydrogel that has been impregnated and vacuumed and released is spread out with colored epoxy resin mixture and cured at room temperature of about 30°C to obtain a transparent radiative temperature-regulating board based on corn stalk. The board is orange-yellow in sunlight.
[0045] Example 3 The method for preparing the temperature-regulating transparent sheet material based on corn stalks adopts the following operation steps: (1) Preparation of eutectic solvent: 63.0g of oxalic acid dihydrate and 69.6g of choline chloride are mixed evenly and stirred continuously in a water bath at 90℃ for 1.5h until there are no impurities in the solution and no crystals precipitate after cooling.
[0046] (2) Pretreatment of corn stalks: Weigh 100g of clean and dry corn stalks, add 2g of eutectic solvent, add deionized water to make the total mass 400g, heat for 60min, the maximum temperature is 165℃, and the holding time is 60min.
[0047] (3) High-temperature treatment of pretreated corn stalks: Weigh 100g of corn stalks obtained after the pretreatment with an absolute dry weight, add NaOH solution made by adding water to 75g NaOH and Na2S solution made by adding water to 24.38g Na2S, add deionized water to make the total liquid mass reach 400g, i.e., the liquid ratio is 1:4, the high-temperature treatment temperature is 165℃, the heat preservation time is 60min, and after the reaction is completed, wash it twice with 10L tap water.
[0048] (4) Decolorization treatment: Weigh 100g of corn stalks obtained after the high-temperature treatment, add 40g of 5% NaClO2 solution, add deionized water to make the total mass of the solution (solid-liquid mixture) 1000g, add 10% oxalic acid solution to pH=1.5, add 600g of eutectic solvent, adjust the water bath temperature to 75℃ and heat for 100min. After heating, dilute and wash three times with 7.7L tap water to obtain lignocellulose.
[0049] (5) Mercerization treatment: 100g of oven-dry weight of high-temperature decolorized lignocellulose is completely immersed in a 170g / L NaOH solution. The treatment temperature is 20℃ and the treatment time is 45min.
[0050] (6) The treated lignocellulose is washed with 28L of tap water and stirred vigorously until neutral to obtain corn stalk cellulose hydrogel.
[0051] (7) Infiltration treatment: Dissolve 1.2g of CuCl2·6H2O epoxy resin in 2g of acetone, mix 40g of epoxy resin a and 20g of epoxy resin b evenly, then immerse 20g of the oven-dry weight of the corn stalk cellulose hydrogel in the epoxy resin, and perform a vacuum-release cycle. The vacuuming time is 10 minutes, and the process is repeated 10 times.
[0052] (8) Curing and molding process: The corn stalk cellulose hydrogel that has been impregnated and vacuumed and released is spread out with colored epoxy resin mixture and cured at room temperature of about 30°C to obtain a radiation temperature-regulating transparent board based on corn stalk. The board is light blue in sunlight.
[0053] Comparative Example 1 The method for preparing boards based on corn stalks adopts the following steps: (1) High temperature treatment of corn stalks: Weigh 100g of clean and dry corn stalks, add NaOH solution made by adding water to 75g of NaOH, and Na2S solution made by adding water to 24.38g of Na2S. Add deionized water to make the total liquid mass reach 400g, i.e., the liquid ratio is 1:4. The high temperature treatment temperature is 165℃ and the heat preservation time is 60min. After the reaction is completed, wash it twice with 10L of tap water.
[0054] (2) Decolorization treatment: Weigh 100g of corn stalks obtained after the high-temperature treatment, add 40g of 5% NaClO2 solution, add deionized water to make the total mass of the solution (solid-liquid mixture) 1000g, add 10% oxalic acid solution until pH=1.5, adjust the water temperature to 75℃ and heat for 100min. After heating, dilute and wash three times with 7.7L tap water.
[0055] (3) Mercerization treatment: 100g of oven-dry weight of high-temperature decolorized lignocellulose is completely immersed in a 170g / L NaOH solution. The treatment temperature is 20℃ and the treatment time is 45min.
[0056] (4) The treated lignocellulose is washed with 28L of tap water and stirred vigorously until neutral to obtain corn stalk cellulose hydrogel.
[0057] (5) Infiltration treatment: Dissolve 1.2g of CoCl2·6H2O epoxy resin in 2g of acetone, mix 40g of epoxy resin a and 20g of epoxy resin b evenly, then take 20g of the oven-dry weight of the corn stalk cellulose hydrogel and impregnate it in the epoxy resin, and perform a vacuum-release repeating operation. The vacuum time is 10 minutes, and the operation is repeated 10 times.
[0058] (6) Curing and molding process: The corn stalk cellulose hydrogel that has been impregnated and vacuumed and released is spread out with colored epoxy resin mixture and cured at room temperature of 30°C to obtain a temperature-regulating transparent board based on corn stalk. The board is light red in sunlight.
[0059] Comparative Example 2 The method for preparing boards based on corn stalks adopts the following steps: (1) Pretreatment of corn stalks: Weigh 100g of clean and dry corn stalks, add deionized water to make the total mass 400g, heat for 60min, the maximum temperature is 165℃, and the heat preservation time is 60min.
[0060] (2) High-temperature treatment of pretreated corn stalks: Weigh 100g of corn stalks obtained after the pretreatment with an absolute dry weight, add NaOH solution made by adding water to 75g NaOH and Na2S solution made by adding water to 24.38g Na2S, add deionized water to make the total liquid mass reach 400g, the liquid ratio is 1:4, the high-temperature treatment temperature is 165℃, the heat preservation time is 60min, and after the reaction is completed, wash it twice with 10L tap water.
[0061] (3) Decolorization treatment: Weigh 100g of corn stalks obtained after the high-temperature treatment, add 40g of 5% NaClO2 solution, add deionized water to make the total mass of the solution 1000g, add 10% oxalic acid solution until pH=1.5, adjust the water temperature to 75℃ and heat for 100min. After heating, dilute and wash three times with 7.7L tap water.
[0062] (4) Mercerization treatment: 100g of oven-dry weight of high-temperature decolorized lignocellulose is completely immersed in a 170g / L NaOH solution. The treatment temperature is 20℃ and the treatment time is 45min.
[0063] (5) The treated lignocellulose is washed with 28L of tap water and stirred vigorously until neutral to obtain corn stalk cellulose hydrogel.
[0064] (6) Infiltration treatment: Dissolve 1.2g of CoCl2·6H2O epoxy resin in 2g of acetone, mix 40g of epoxy resin a and 20g of epoxy resin b evenly, then immerse 20g of the oven-dry weight of the corn stalk cellulose hydrogel in the epoxy resin, and perform a vacuum-release cycle. The vacuuming time is 10 minutes, and the process is repeated 10 times.
[0065] (7) Curing and molding process: The corn stalk cellulose hydrogel that has been impregnated and vacuumed and released is spread out with colored epoxy resin mixture and cured at room temperature of 30°C to obtain a temperature-regulating transparent board based on corn stalk. The board is light red in sunlight.
[0066] Comparative Example 3 The method for preparing boards based on corn stalks adopts the following steps: (1) Preparation of low eutectic solvent: 63.0g of oxalic acid dihydrate and 69.6g of choline chloride are mixed evenly and stirred continuously in a water bath at 90℃ for 1.5h until there are no impurities in the solution and no crystals precipitate after cooling.
[0067] (2) High-temperature treatment of corn stalks: Weigh 100g of clean and dry corn stalks, add NaOH solution made by adding water to 75g of NaOH, and Na2S solution made by adding water to 24.38g of Na2S. Add deionized water to make the total liquid mass reach 400g. The liquid ratio is 1:4. The high-temperature treatment temperature is 165℃ and the heat preservation time is 60min. After the reaction is completed, wash the corn stalks twice with 10L of tap water.
[0068] (3) Decolorization treatment: Weigh 100g of corn stalks obtained after the high-temperature treatment, add 40g of 5% NaClO2 solution, add deionized water to make the total mass of the solution (solid-liquid mixture) 1000g, add 10% oxalic acid solution until pH=1.5; add 600g of eutectic solvent, adjust the water bath temperature to 75℃ and heat for 100min. After heating, dilute and wash three times with 7.7L tap water.
[0069] (5) Mercerization treatment: 100g of oven-dry weight of high-temperature decolorized lignocellulose is completely immersed in a 170g / L NaOH solution. The treatment temperature is 20℃ and the treatment time is 45min.
[0070] (6) The treated lignocellulose is washed with 28L of tap water and stirred vigorously until neutral to obtain corn stalk cellulose hydrogel.
[0071] (7) Infiltration treatment: Dissolve 1.2g of CoCl2·6H2O epoxy resin in 2g of acetone, mix 40g of epoxy resin a and 20g of epoxy resin b evenly, then immerse 20g of the oven-dry weight of the corn stalk cellulose hydrogel in the epoxy resin, and perform a vacuum-release cycle. The vacuuming time is 10 minutes, and the process is repeated 10 times.
[0072] (9) Curing and molding process: The corn stalk cellulose hydrogel that has been impregnated and vacuumed and released is spread out with the colored epoxy resin mixture and cured at room temperature of 30°C to obtain a transparent radiative temperature-regulating board based on corn stalks. The board is light red in sunlight.
[0073] Taking the temperature-adjustable transparent sheet material prepared in Example 1 as an example, it was compared with Comparative Examples 1-3. Samples were taken from the corn stalk cellulose hydrogel initially prepared in the above preparation steps, and the lignin content and α-cellulose purity were determined. Lignin was detected using the Klason method (TAPPI T222), and α-cellulose purity was detected using the nitric acid-ethanol method (GB / T 744).
[0074] In addition, the light transmittance of the plates obtained in Comparative Examples 1, 2, 3 and Example 1 was measured using a spectrophotometer and integrating sphere.
[0075] The test results are shown in Table 1 below.
[0076]
[0077] The above test results show that the purity of α-cellulose in the intermediate product corn stalk cellulose is a key indicator affecting the light transmittance of the board. The purification method proposed in this invention, through pretreatment steps and the use of eutectic solvents, can obtain an intermediate product (corn stalk cellulose hydrogel) with high α-cellulose purity, resulting in a board with high light transmittance.
[0078] For the transmittance curves of the boards prepared in Examples 1-3, please refer to [the graphs]. Figure 1 As shown in the figure, the highest peak transmittance of the plate in Example 1 occurred between wavelengths of 650nm and 700nm, and the plate was generally red; the highest peak transmittance of the plate in Example 2 occurred between wavelengths of 600nm and 650nm, and the plate was generally yellow; the highest peak transmittance of the plate in Example 3 occurred between wavelengths of 400nm and 450nm, and the plate was generally blue.
[0079] The board obtained in Example 1 was placed outdoors in an unobstructed location to test its temperature regulation effect. See [link to relevant documentation]. Figure 2 .Depend on Figure 2 The results show that it can achieve excellent passive radiative temperature regulation performance compared with the actual temperature.
[0080] The preparation method of the temperature-adjustable transparent sheet material based on corn stalks provided by the present invention has been described in detail above. The specific embodiments described above should not be construed as limiting the scope of protection of the present invention. Any alternative improvements or modifications made to the embodiments of the present invention by those skilled in the art fall within the scope of protection of the present invention.
[0081] Any aspects of this invention not described in detail are well-known to those skilled in the art.
Claims
1. A method for preparing a temperature-adjustable transparent sheet material based on corn stalks, characterized in that, The following steps are included: (1) Preparation of corn straw cellulose hydrogel by purification of corn straw; S1, Preprocessing Add water and eutectic solvent to corn stalks, raise the temperature to 165℃±5℃ within 60-70 minutes, and keep it at that temperature for 50-60 minutes; S2, High-temperature treatment Add active alkali and continue to keep warm at 165℃±5℃ for 50-60 minutes. After the reaction is complete, wash with water. S3, Decolorization treatment The product obtained in step S2 was added to NaClO2, a eutectic solvent and water, and treated in a water bath at 75°C for 100-120 min at pH=1.
5. Then it was diluted and washed with water to obtain lignocellulose. S4, Mercerizing treatment The lignocellulose obtained in step S3 was completely immersed in NaOH solution at a temperature of 20℃±1℃ for 45-60 min; then it was washed with water and vigorously stirred until neutral to obtain corn straw cellulose hydrogel. (2) Osmosis treatment Epoxy resin a glue, epoxy resin b glue, and dyeing solution are mixed evenly, and the corn straw cellulose hydrogel obtained in step (1) is immersed in the dyed colored epoxy resin, and the vacuum-release repeated operation is performed. (3) Curing and molding Spread the mixture obtained from step (2) evenly and let it cure at room temperature to obtain the final product.
2. The preparation method according to claim 1, characterized in that, The eutectic solvent in step (1) is prepared as follows: Oxalic acid and choline chloride are mixed uniformly at a molar ratio of 1:1 and stirred in a 90°C water bath for 1.5-2 hours until there are no impurities in the solution. The solution is then cooled until no crystals precipitate. In step S1, water is added to maintain the liquid ratio at 1:
4. The amount of the eutectic solvent used in step S1 is 2%-3% of the dry weight of the corn stalks.
3. The preparation method according to claim 1, characterized in that, In step (1), the amount of active alkali used in the S2 high-temperature treatment is calculated as 25%-30% of the oven-dry weight of the corn stalks used in this step; the active alkali is NaOH and Na2S; the degree of sulfidation in this step is 25%-30%; and the liquid ratio is 1:
4.
4. The preparation method according to claim 1, characterized in that, In step (1), the amount of NaClO2 used in the S3 decolorization treatment is 2%-5% of the dry weight of the corn stalks used in this step, and the amount of eutectic solvent is 6-9 times the dry weight of the corn stalks used in this step; the amount of water added in S3 is such that the dry weight of the corn stalks treated in this step accounts for 10% of the total weight of all solid-liquid mixtures except for the eutectic solvent.
5. The preparation method according to claim 1, characterized in that, In step (2), the mass ratio of epoxy resin a to epoxy resin b is 2-3:
1.
6. The preparation method according to claim 1, characterized in that, In step (2), the staining solution is CoCl2·6H2O acetone solution, FeCl3·2H2O solution or CuCl2·2H2O solution, and the amount of staining solution added is 2%-5% of the total mass of epoxy resin.
7. The preparation method according to claim 1, characterized in that, Step (2) involves mixing epoxy resin a, dyeing solution, epoxy resin b, and corn stalk cellulose hydrogel in that order. The mixture is stirred evenly to obtain colored epoxy resin.
8. The preparation method according to claim 1, characterized in that, In step (2), the vacuuming time is 10-15 minutes, and it is repeated 5-10 times.
9. The preparation method according to claim 1, characterized in that, In step (3), room temperature curing refers to curing at 25℃-35℃.